Strategic Analysis of Logistical Processes in an OEM Automotive Manufacturing Plant in Spain - Craiss, Moritz (2025)
This master’s thesis examines intralogistics processes at an automotive manufacturing plant in Spain, focusing on buffer management and large-load carrier replenishment. The simultaneous assembly of ICE and BEV platforms in the future significantly increases complexity due to parts variability, storage demand, and material flow variability. Using the LSS methodology and the DMAIC framework, the current processes are mapped, measured, and evaluated using logistics performance indicators. An ABC/XYZ analysis was conducted to classify parts and create tailored recommendations based on part characteristics. The thesis proposes a segment-based strategy for large-load carriers and an optimized re-order point system. The recommendations aim to improve logistics operations, enhance space utilization, and prepare the plant for the upcoming BEV integration in the assembly.